Pregnancy attitudes and contraceptive use among young adults with histories of foster care. (November 2018) - Combs, Katie Massey; Brown, Samantha M.; Begun, Stephanie; Taussig, Heather
Abstract: Introduction: This study examined pregnancy attitudes and contraceptive use among young adults with histories of foster care. Methods: 209 female and male young adults, aged 18–22, with histories of foster care were interviewed about their intentions and feelings towards pregnancy. Respondents were then categorized as having pro-pregnancy (i.e., having positive pregnancy intentions and happy feelings about pregnancy), ambivalent (either intentions or happy feelings), or anti-pregnancy (no intentions and unhappy feelings) attitudes. Participants also reported their past-year contraceptive use, and the relationship between pregnancy attitudes and contraceptive use was subsequently explored for the overall sample, and by sex and history of pregnancy using Chi-square tests. Results: Only 13.4% of participants had positive pregnancy intentions, though 41.9% reported that they would feel happy with a pregnancy. Over half (55.9%) of participants were anti-pregnancy, a third (32.8%) were ambivalent and 11.3% were pro-pregnancy. Compared to females, males were more likely to have positive pregnancy intentions (18.6% vs. 7.8%, p = .03) and to be pro-pregnancy (16.5% vs. 5.6%, p = .04). No differences in pregnancy attitudes were found as a function of pregnancy history. Consistent contraceptive use was significantly associated with pregnancy attitudes; 22.2% of pro-pregnancy participants reported consistent contraceptive use versus 52.9% of ambivalent and 62.2% of anti-pregnancy participants. Discussion: In this exploratory study, few participants held pro-pregnancy attitudes and a high percentage of participants who were anti-pregnancy did not use contraception consistently. Although studies with larger samples examining this topic are needed, professionals should distinguish between young adults' intentions and feelings about pregnancy in an effort to better address contraceptive needs. Highlights: Few emerging adults (13.4%) with a history of foster care desired to become pregnant or a parent in the next year. Nearly half (41.4%) of participants with negative feelings or intentions towards pregnancy used contraception inconsistently. Professionals should distinguish between pregnancy intentions and feelings in order to better address contraceptive needs. Professionals should not assume that young people who do not use consistent contraception desire pregnancy.